MANAJEMEN PELAYANAN TERPADU SATU PINTU (PTSP) DI MAN KOTA PALANGKA RAYA - Masturo Fikrin; Dakir Dakir; Slamet Riyadi (Jurnal Manajemen Pendidikan, 2026)
Public demand for fast, transparent, and accountable services has encouraged educational institutions to innovate their administrative systems. One such innovation is the One-Stop Integrated Service (PTSP), which centralizes various administrative services in a single unit to improve effectiveness and efficiency. This study aims to analyze PTSP management in improving administrative service quality at MAN Kota Palangka Raya using a qualitative descriptive approach. Data were collected through observation, interviews, and documentation involving the head of administration, PTSP officers, and service users. The results show that PTSP management is implemented through planning, organizing, and implementing service stages integrated into one unit. The novelty lies in developing a PTSP management model integrating management functions, service excellence ethics (5S principles), and administrative digitalization in the madrasah context. The study reveals the interrelationship between service governance, officer behavior, and technology use in improving public education service quality, producing empirical findings of increased service time efficiency and user satisfaction as PTSP management success indicators in Islamic educational institutions.